2001
DOI: 10.1007/s004040000151
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of endometrial hyperplasia

Abstract: Seventy-seven patients with endometrial hyperplasia, 48 with simple hyperplasia without atypia (SH), 17 with complex hyperplasia without atypia (CH), one with simple hyperplasia with atypia (SHA), and 11 with complex hyperplasia with atypia (CHA) were prospectively followed-up by total curettage every 12 months for 3 years. Progression to carcinoma occurred in only one of the 77 patients; she showed grade 1 adenocarcinoma. The overall regression rates were 79% for SH, 100% for SHA, 94% for CH, and 55% for CHA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 3 publications
1
16
1
Order By: Relevance
“…Therefore, the experience of women diagnosed with SH or CH in our study is likely representative of the general population of women with nonatypical EH. Our study design represents an improvement over previous studies that lacked control groups (Kurman et al, 1985;Lindahl and Willen, 1994;Terakawa et al, 1997;Tabata et al, 2001;Horn et al, 2004;Baak et al, 2005), included few women with EH who developed carcinoma (Kurman et al, 1985;Feldman et al, 1994;Lindahl and Willen, 1994;Horn et al, 2004;Baak et al, 2005) or relied on short follow-up (Terakawa et al, 1997;Tabata et al, 2001). Previous studies expressed risk as crude percentages -e.g., 20% of patients with non-atypical AH (Ferenczy and Gelfand, 1989) or 29% of patients with AH (Kurman et al, 1985) progress to cancerrather than population-based rate ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the experience of women diagnosed with SH or CH in our study is likely representative of the general population of women with nonatypical EH. Our study design represents an improvement over previous studies that lacked control groups (Kurman et al, 1985;Lindahl and Willen, 1994;Terakawa et al, 1997;Tabata et al, 2001;Horn et al, 2004;Baak et al, 2005), included few women with EH who developed carcinoma (Kurman et al, 1985;Feldman et al, 1994;Lindahl and Willen, 1994;Horn et al, 2004;Baak et al, 2005) or relied on short follow-up (Terakawa et al, 1997;Tabata et al, 2001). Previous studies expressed risk as crude percentages -e.g., 20% of patients with non-atypical AH (Ferenczy and Gelfand, 1989) or 29% of patients with AH (Kurman et al, 1985) progress to cancerrather than population-based rate ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20 200 women in the United States who undergo hysterectomy receive a primary hospital discharge diagnosis of EH each year (Keshavarz et al, 2002), but progression risks for EH have not been accurately characterised in rigorous populationbased studies (Silverberg, 2000). Current management of EH relies on largely historical data from studies that lacked adequate control groups (Kurman et al, 1985;Feldman et al, 1995;Terakawa et al, 1997;Tabata et al, 2001;Horn et al, 2004;Baak et al, 2005) and were limited by sample size (Feldman et al, 1995;Tabata et al, 2001), short follow-up (Feldman et al, 1995;Terakawa et al, 1997;Tabata et al, 2001), suboptimal statistical methods (Kurman et al, 1985;Pettersson et al, 1985;Feldman et al, 1995;Terakawa et al, 1997;Tabata et al, 2001;Horn et al, 2004), and minimal clinical and treatment information (Kurman et al, 1985;Pettersson et al, 1985;Terakawa et al, 1997;Tabata et al, 2001;Horn et al, 2004). Endometrial hyperplasia diagnoses can misclassify disease severity because of biopsy sampling errors (Zaino, 2000;Trimble et al, 2006;Zaino et al, 2006) or the community pathologists' reported tendency to overestimate lesion severity (Silverberg, 2000).…”
mentioning
confidence: 99%
“…The rate of progression to endometrial carcinoma has been estimated to be 0-3% in patients without atypia, 0-8% in patients with simple atypical hyperplasia, and 9-29% in patients with complex atypical endometrial hyperplasia (CAEH) (Kurman et al, 1985;Tabata et al, 2001). The risk of concomitant endometrial carcinoma has been reported to be 20-59% in CAEH (Lambert et al, 1994;Kimura et al, 2003;Valenzuela et al, 2003;Antonsen et al, 2012;Morotti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Tabata et al observed spontaneous regression of endometrial hyperplasia in all risk groups, and the overall regression rates were 79% for SH, 100% for AH, 94% for CH, and 55% for CAH; regression occurred mostly within the first year (Tabata et al, 2001). Clearly, results were improved with a follow-up of longer duration.…”
Section: Discussionmentioning
confidence: 83%
“…The SH regression rate has been reported to be 74-80%, with a 1% progression rate ( Tabata et al, 2001;Montgomery et al, 2004). In a recent study, complete resolution was found in 72% of 60 cases after 3 months of progestin therapy, with no progression (Tasci et al, 2014).…”
Section: Discussionmentioning
confidence: 96%